Mechanical and biological behavior of ultrafine-grained Ti alloy aneurysm clip processed using high-pressure torsion. (April 2017) - Um, Ho Yong; Park, Byung Ho; Ahn, Dong-Hyun; Abd El Aal, Mohamed Ibrahim; Park, Jaechan; Kim, Hyoung Seop
Abstract: Severe plastic deformation (SPD) has recently been advanced as the main process for fabricating bulk ultrafine grained or nanocrystalline metallic materials, which present much higher strength and better bio-compatibility than coarse-grained counterparts. Medical devices, such as aneurysm clips and dental implants, require high mechanical and biological performance (e.g., stiffness, yield strength, fatigue resistance, and bio-compatibility). These requirements match well the characteristics of SPD-processed materials. Typical aneurysm clips are made of a commercial Ti-6Al-4V alloy, which has higher yield strength than Ti. In this work, Ti and Ti-6Al-4V workpieces were processed by high-pressure torsion (HPT) to enhance their mechanical properties. Tensile tests and hardness tests were performed to evaluate their mechanical properties, and their microstructure was investigated. The hardness and yield stress of the HPT-processed Ti are comparable to those of the initial Ti-6Al-4V due to significantly refined microstructure. Finite element analyses for evaluating the opening performance of a specific geometry of the YASARGIL aneurysm clip were carried out using mechanical properties of the initial and HPT-processed Ti and Ti-6Al-4V. These results indicate that SPD-processed Ti could be a good candidate to substitute for Ti-6Al-4V in aneurysm clips.